Voyage to Sandy Bay - Seaforth, Sybil (Harlow : Longman, 1997)
Dorothy has just passed her Common Entrance and is looking forward to going to High School when her mother decides to move to Skiff Bay. Dorothy, initially reluctant, soon makes new friends and, more excitingly, meets the son of her socially superior next-door-neighbours. The story of how Dorothy grows up is interwoven with strong themes of social and racial prejudice that Dorothy must face in the Caribbean.
NLJCols20082021
Keywords: Jamaica -- Fiction; Jamaica; Fiction